2014
DOI: 10.3945/jn.113.185298
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolizable Energy of Dietary Resistant Maltodextrin Is Variable and Alters Fecal Microbiota Composition in Adult Men

Abstract: Resistant maltodextrin (RM) is a novel soluble, nonviscous dietary fiber. Its metabolizable energy (ME) and net energy (NE) values derived from nutrient balance studies are unknown, as is the effect of RM on fecal microbiota. A randomized, placebo-controlled, double-blind crossover study was conducted (n = 14 men) to determine the ME and NE of RM and its influence on fecal excretion of macronutrients and microbiota. Participants were assigned to a sequence consisting of 3 treatment periods [24 d each: 0 g/d RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 42 publications
1
41
0
2
Order By: Relevance
“…Some single-meal or single-day human studies have shown benefits of~10 g of dietary fiber to lessen perceived hunger, including the present study, but not all dietary fibers compared at that dose had significant satiating effects, as described above [26]. Fibersol-2 was well tolerated at 25 and 50 g/d for 14 days, with some reports of increased flatus [20]. More systematic dose/response studies of satiety effects across fiber types and products might be helpful.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Some single-meal or single-day human studies have shown benefits of~10 g of dietary fiber to lessen perceived hunger, including the present study, but not all dietary fibers compared at that dose had significant satiating effects, as described above [26]. Fibersol-2 was well tolerated at 25 and 50 g/d for 14 days, with some reports of increased flatus [20]. More systematic dose/response studies of satiety effects across fiber types and products might be helpful.…”
Section: Discussionmentioning
confidence: 48%
“…A 24-day randomized, double-blind placebo-controlled trial in 14 men showed that ingesting 25 or 50 g of this fiber per day modestly but significantly decreased total metabolizable energy intake compared with the placebo [20]. Additional studies that address possible mechanisms of regulation of energy intake by such dietary fibers are needed.…”
mentioning
confidence: 96%
“…Fiber contains a given amount of protein which is usually undigestible and could influence the protein digestibility value. This protein value within fiber increases fecal nitrogen concentration [75]. Hence, undigested protein in the fiber source could influence dietary protein digestibility.…”
Section: Interactions Of Dietary Fibre On Protein Bioavailabilitymentioning
confidence: 99%
“…Les produits de cette fermentation qui sont, par exemple, les acides gras à chaîne courte (acétate, propionate, butyrate et leurs dérivés) interagissent avec les cellules intestinales, notamment les cellules épithéliales, immunitaires et nerveuses. Ils stimulent leurs fonctions endocrines en induisant la sécrétion de défensines, des peptides naturels ayant un rôle antimicrobien, la sécrétion d'hormones, comme le GLP1 (glucagon like peptide one) ou le NPY (neuropeptide Y) qui activent le système nerveux entérique et induisent la maturation [38][39][40]. Les probiotiques, quant à eux, sont constitués de micro-organismes vivants (levures, bactéries) normalement inoffensifs.…”
Section: Synthèse Revuesunclassified